ANALYSIS OF STUDENT LEARNING ERRORS IN COMPLETING THE OPERATIONS OF CLASS V ROUND NUMBERS OF SD NEGERI MALEWA - Agnes Grasela Besu; Akina Akina; Nuraini Nuraini (Universitas Tadulako, 2021)
This study aims to describe the types of student learning errors in completing integer arithmetic operations and to determine the factors that cause student learning errors in completing integer arithmetic operations. This research is a qualitative descriptive study based on the polya steps. The subjects in this study were all class V, amounting to 3 students, and the sampling technique was using tests, interviews, and documentation. The instrument in this study was a test in the form of an integer arithmetic operation story question consisting of 5 questions. The results of this study can be concluded that: (1) misunderstanding of the problem, namely students do not write down what is known and asked, (2) errors in making plans, namely students do not determine the strategy and methods to be used to make problem solving solutions, (3) errors in implementing the plan is that students do not correctly write down the steps or work procedures in solving the problem (4) errors in re-checking, namely students incorrectly seeing (checking) the results obtained. The factors that cause student learning errors in completing integer arithmetic operations are (1) the student is in a hurry, (2) is afraid of a shortage of time, (3) the student is not able to solve the problem, (4) the student is not careful in working on story problems, ( 5) the atmosphere is less conducive